ORGANIC FARMING AND MARKETING CHALLENGES: A CASE STUDY OF HARYANA - Saini, Shubham; Meena, Hukam Singh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The growing issues of health among people and increasing awareness for organic products has directed number of people towards organic consumption. This also led the number of opportunities for farmers to produce organic food. Along with the emerging opportunities, farmers are also facing challenges, thus this study aims to explore the limitations and challenges faced by farmers to switch over organic productions. The sample size for this study comprised 100 farmers from various districts in Haryana, which includes both organic as well as conventional producers. For this study, sequential form of mixed method is used, that is quantitative as well as qualitative. The major findings of qualitative analysis revealed six major market challenges namely, less production, shortage of warehousing facility, lack of government support especially in form of subsidy and promotion, inadequate demand of crops, market price issues and high cost of transportation. This study is to understand market challenges for organic farmers in a developing country like India. The findings of this study will contribute to various stakeholders at policy level to build better strategies to successful promotion of organic farming. This will definitely contribute in fulfilling healthy consumption in India as well as reaching the goals of sustainable development goals.